KECERDASAN MAJEMUK DAN IMPLIKASINYA DALAM PENDIDIKAN - Dia Nita (Jurnal Psikologi Universitas HKBP Nommensen, 2020)
Multiple Intelligence and Its Implications in Education. Dr. Howard Gardner developed the Multiple Intelligence theory which is able to provide a new theory with several types of intelligence that can reflect the way of interacting in the world. Gardner rejects the notion that human knowledge is one unit and that individuals only have a single intelligence. There are nine types of multiple intelligences put forward by Gardner, including: linguistic intelligence, logical-mathematical intelligence, visual intelligence, musical intelligence, kinesthetic intelligence, interpersonal intelligence, intrapersonal intelligence, and naturalist intelligence, existential intelligence. The theory of multiple intelligences is able to have a positive influence in learning, such as making teachers develop learning methods, providing optimal learning outcomes and being able to make children not feel bored while learning.